Solving the single-country sample problem in cultural distance studies - Brouthers, Lance Eliot; Marshall, Victor B; Keig, Dawn L (Journal of International Business Studies, 2016)
Selecting appropriate samples in cultural distance research is vital to producing valid empirical results. Over 80% of empirical cultural distance studies use a sample comprised of either a single home country with varying host countries or a single host country with varying home countries. When difference scores are used in the calculation of cultural distance based on single-country samples the resulting cultural distance measures typically are highly correlated with one or more of the varying countries’ underlying national culture dimensions, making it impossible to determine whether findings are due to cultural distance or to varying countries’ national culture effects. This is referred to as a confounded variables problem and means that for an overwhelming number of cultural distance studies, we cannot with certainty have confidence in the verity of their findings. To resolve this uncertainty we propose that cultural distance scholars select samples comprised of at least two home/host countries. We empirically demonstrate that two-country samples where most of the national culture dimensions for the two countries differ create certitude with respect to results, eliminating the cultural distance confounded variables problem. We describe the single-country sample problem, illustrate the proposed a priori two-country solution, and suggest avenues for future research.